PENGEMBANGAN LABORATORIUM VIRTUAL SEBAGAI MEDIA PRAKTIKUM ALTERNATIF PADA MATA PELAJARAN BIOLOGI DI SMA - ATIKAH, CUCU; Achyani, Achyani; Muhfahroyin, Muhfahroyin (BIOLOVA, 2023)
This development research aims to produce a product in the form of an Android-based Catalase Enzyme Test V-Lab application which is expected to be used as an alternative practicum medium for Biology subjects in SMA. in Biology subjects that can support practical activities in the learning process. The research was conducted using the RND (Research and Development) method with the ADDIE development model. The results showed that the results of expert validation from 4 aspects obtained scores with "very good" criteria consisting of the percentages: media design experts 97%, material experts 92%, linguists experts 96%, IT experts 90%. The results of the limited trial applied in the field obtained the results of small group trials of students of 94%, teacher responses of 95%, large group trials of 94%, and evaluation of 97%, with the criteria of “very good”. Thus, it can be concluded that the V-Lab Catalase Enzyme Test application that has been made has met the "very good" eligibility standard, so it is suitable to be used as an alternative practicum medium in Biology learning in high school.